2016
DOI: 10.1177/1948550616644297
|View full text |Cite
|
Sign up to set email alerts
|

Some Evidence for a Gender Gap in Personality and Social Psychology

Abstract: This research examined a possible gender gap in personality and social psychology. According to membership demographics from the Society for Personality and Social Psychology (SPSP), women and men are represented near parity in the field. Yet despite this equal representation, the field may still suffer from a different type of gender gap. We examined the gender of first authors in two major journals, citations to these articles, and gender of award recipients. In random samples of five issues per year across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 21 publications
3
39
1
3
Order By: Relevance
“…A similar gap was found in social and personality psychology, a field in which women outnumber men according to membership statistics from the Society for Personality and Social Psychology (Brown & Goh, 2016). But despite this emerging membership trend, the authors found that men receive more awards than women (Brown & Goh, 2016). Their results mirror findings in other areas, such as an analysis of awards data from 13 STEM societies revealing that men received more awards than women, and this number was higher than expected based on the proportion of male to female nominees in the pool (Lincoln et al, 2012).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…A similar gap was found in social and personality psychology, a field in which women outnumber men according to membership statistics from the Society for Personality and Social Psychology (Brown & Goh, 2016). But despite this emerging membership trend, the authors found that men receive more awards than women (Brown & Goh, 2016). Their results mirror findings in other areas, such as an analysis of awards data from 13 STEM societies revealing that men received more awards than women, and this number was higher than expected based on the proportion of male to female nominees in the pool (Lincoln et al, 2012).…”
supporting
confidence: 56%
“…A similar gap was found in social and personality psychology, a field in which women outnumber men according to membership statistics from the Society for Personality and Social Psychology (Brown & Goh, 2016). But despite this emerging membership trend, the authors found that men receive more awards than women (Brown & Goh, 2016).…”
mentioning
confidence: 54%
“…Por otra parte, se están analizando las características y las implicaciones de estudios de la literatura en proyectos de mujeres, lo cual ha dado cuenta de un importante crecimiento de sus trabajos en un estudio de más de 100 años (Tsay & Li, 2017). Específicamente, en psicología, se observa una paridad de género en el número de autores y una asimetría de género que es mucho menor que en la ciencia y en otras disciplinas (González-Álvarez & Cervera-Crespo, 2017), aunque, algunos análisis de la producción en áreas particulares, tal es el caso de la psicología social y de la personalidad revela un mayor porcentaje de artículos publicados y citados desarrollados por hombres (Brown & Goh, 2016).…”
Section: El Análisis Bibliométrico Y Su Estado Del Arte En Psicologíaunclassified
“…Similarly, much (we suspect most) of the discourse about sexist bias in education, academia, STEM, and even psychology emphasizes the difficulties women face (e.g., Brown & Goh, 2016;Greider et al, 2019;Handelsman et al, 2005;Knobloch-Westerwick, Glynn, & Huge, 2013;Ledgerwood, Haines, & Ratliff, 2015;Milkman, Akinola, & Chugh, 2012;Moss-Racusin, Dovidio, Brescoll, Graham, & Handelsman, 2012;National Academies of Sciences, Engineering, and Medicine, 2018;Nature, 2015;Steele, James, & Barnett, 2016;Steinpreis, Anders, & Ritzke, 1999; United States National Academy of Sciences, 2007;Wenneras & Wold, 1997). Nonetheless, women now represent a majority of social psychologists, most of the leadership in at least one of the main social psychology professional organizations (SPSP, 2019), a majority of psychologists (American Psychological Association, 2015, and have been more likely to complete high school, college, and graduate degrees than have men for about 40 years (Sharp, 2010).…”
mentioning
confidence: 99%